Preparation of Fe oxide nanoparticles for environmental applications: arsenic removal - Beker, Ulker; Cumbal, Luis; Duranoglu, Dilek; Kucuk, Ilknur; Sengupta, Arup K. (SPRINGER, 2010)
The objective of this study is to examine the adsorption-desorption behavior of a magnetically active hybrid sorbent (MAHS) material, prepared by dispersing colloid-like hydrated iron oxide particles in the outer periphery of a macroporous ion-exchange resin (Amberlite XAD-2). The experimental results show that the new sorbent material can simultaneously remove arsenic (V) and a chlorinated organic compound (2,6-dichlorophenol [2,6-DCP]) from aqueous solutions at around neutral pH. The recovery of arsenic and 2,6-DCP from MAHS was conducted using a regenerant containing 50% (v/v) CH(3)OH + 3% (w/v) NaOH. In less than 10 bed volumes of regenerant, more than 90% of As(V) and 2,6-DCP were recovered.
Keywords: Arsenic; Ion exchange; Magnetic sorbent; Hydrated Fe oxide; Safe water; MICELLAR-ENHANCED ULTRAFILTRATION; SOLVENT-IMPREGNATED RESINS; DRINKING-WATER; COATED SAND; IRON; GROUNDWATER; COAGULATION; EXTRACTION; SORBENT; Engineering; Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Water Resources